Dynamic palmitoylation regulates trafficking of K channel interacting protein 2 (KChIP2) across multiple subcellular compartments in cardiac myocytes. (October 2019) - Murthy, Akshay; Workman, Samuel W.; Jiang, Min; Hu, Junping; Sifa, Ismat; Bernas, Tytus; Tang, Wanchun; Deschenes, Isabelle; Tseng, Gea-Ny
Abstract: Background: K channel interacting protein 2 (KChIP2), initially cloned as Kv4 channel modulator, is a multi-tasking protein. In addition to modulating several cardiac ion channels at the plasma membrane, it can also modulate microRNA transcription inside nuclei, and interact with presenilins to modulate Ca release through RyR2 in the cytoplasm. However, the mechanism regulating its subcellular distribution is not clear. Objective: We tested whether palmitoylation drives KChIP2 trafficking and distribution in cells, and whether the distribution pattern of KChIP2 in cardiac myocytes is sensitive to cellular milieu. Method: We conducted imaging and biochemical experiments on palmitoylatable and unpalmitoylatable KChIP2 variants expressed in COS-7 cells and in cardiomyocytes, and on native KChIP2 in myocytes. Results: In COS-7 cells, palmitoylatable KChIP2 clustered to plasma membrane, while unpalmitoylatable KChIP2 exhibited higher cytoplasmic mobility and faster nuclear entry. The same differences in distribution and mobility were observed when these KChIP2 variants were expressed in cardiac myocytes, indicating that the palmitoylation-dependent distribution and trafficking are intrinsic properties of KChIP2. Importantly, acute stress in a rat model of cardiac arrest/resuscitation induced changes in native KChIP2 resembling those of KChIP2 depalmitoylation, promoting KChIP2 nuclear entry. Conclusion: The palmitoylation status of KChIP2 determines its subcellular distribution in cardiac myocytes. Stress promotes nuclear entry of KChIP2, diverting it from ion channel modulation at the plasma membrane to other functions in the nuclear compartment. Highlights: The literature shows that KChIP2 can serve different functions depending on its subcellular localization. Palmitoyl cycles control KChIP2 trafficking between plasma membrane and nucleus. Acute stress triggers nuclear entry of KChIP2 in cardiac myocytes. Nuclear entry diverts KChIP2's role from channel modulation to other functions inside nucleus.